Penggunaan model discovery learning berbantuan media cerita fiksi untuk meningkatkan membaca cerita siswa kelaS IV sekolah dasar - Sinta Rosita; Agni Muftianti; Ruli Setiyadi (IKIP Siliwangi, 2024)
This research shows that the reason that grade 4 students do not show interest in reading fiction stories in elementary school is because the learning model is monotonous, not suitable for grade 4 students, so students get bored quickly when studying. This can happen. Researchers use mixed methods that combine explanatory sequential design and discovery learning models to increase students' interest in reading fiction stories. Various tools are used to collect data, such as tests, student questionnaires, teacher questionnaires, teacher interviews, teacher observation forms, and student observation forms, which are processed quantitatively and qualitatively. Research samples consisting of 36 students at Sukasari Elementary School, Sukasari Village, Gununghar District, West Bandung Regency. From the research results we can conclude that the learning model was found to be very good in the novel content reading abilities of class IV students. It can be proven that the post-test results are good and increase significantly at the end of student learning.